Anti-influenza antibody - TONOUCHI, KEISUKE; TAKAHASHI, YOSHIMASA; NAKAKO, MAYUMI; ADACHI, YU (2025)
The present application provides a monoclonal antibody, or an antibody fragment thereof, that binds to the hemagglutinin stem region (HA stem region) of influenza A virus.